Klasifikasi dan Estimasi Ketinggian Planetary Boundary Layer (PBL) Menggunakan Data Radiosonde - Carundyatama, Daniar Ihza; Anisa Nabilah; Yosafat Donni Haryanto (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2026)
The Planetary Boundary Layer (PBL) is the atmospheric layer closest to the Earth’s surface that plays a crucial role in weather dynamics. This study aims to classify the types and estimate the heights of the PBL in three regions of Indonesia representing different latitudes using radiosonde data during the period of January–December 2024. Classification was performed using the Potential Temperature Difference (PTD) method, while PBL height estimation utilized the potential temperature gradient, relative humidity, and parcel methods. The results show that at 00:00 UTC, the PBL is dominated by a stable boundary layer (SBL), whereas at 12:00 UTC, there is an increase in variability with the emergence of a neutral boundary layer (NBL) and a convective boundary layer (CBL). Estimates of PBL height ranged from <500 m to >2000 m, with the lowest values generally occurring in the morning and the highest during the JJA period. This study demonstrates that PBL variability in Indonesia is controlled by diurnal cycles, latitudinal differences, and atmospheric thermodynamic conditions, and contributes to the understanding of PBL characteristics in tropical maritime regions.